Kajian Geospasial Untuk Pengembangan Fasilitas Pendukung Destinasi Wisata Di Gorontalo: Literatur Review - Jepril, Jepril; Melo, Ramla Hartini; Pambudi, Moch Rio; Asrul, Asrul (-, 2025)
This study presents a thematic literature review examining the role of Geographic Information Systems (GIS) in developing supporting facilities for tourism destinations, with a specific focus on the Gorontalo region. Analysis of ten selected articles reveals that GIS is effective in identifying facility gaps, classifying tourism sites based on development needs, and designing spatially targeted strategies. GIS offers advantages such as real-time data availability, support for participatory planning, and continuous evaluation, facilitating more accurate, evidence-based policymaking. Additionally, GIS enables integration across sectors such as transportation, local economy, and environmental preservation, enhancing the effectiveness of regional planning. Despite challenges like the need for technical training, limited data availability, and uneven infrastructure access, GIS remains a valuable tool for supporting digital transformation in tourism governance. This study recommends the expansion of GIS as a key instrument for inclusive, efficient, and sustainable tourism planning and destination promotion in Gorontalo